Conocimiento de Enfermería sobre Canalización de vía periférica y la presencia de Flebitis en el Neonato - Florian Villena, Lorena Giuliana (2015)
The descriptive – correlational research study was made at the Neonatology Department of the Hospital Belén, in order to establish the relationship between the level of knowledge of the nurse on the intravenous catheter placement and the presence of neonatal phlebitis. The sample consisted of 30 neonatal nurses and 30 newborn who fulfilled the inclusion criteria. The data collection was obtained from two instruments: “Questionnaire to measure the level of knowledge of the nurse about the intravenous catheter placement” and “Observation guide to identify the presence of phlebitis in neonates”. Statistical analysis was performed using the SPSS statistical software Windows version 22. The Chi Square test was used to determine the relationship. The analysis concluded: 20 porcent of the nurses had a low level of knowledge regarding the intravenous catheter placement in the neonate, 66.7 porcent an average knowledge and 13.3 porcent a high one. 53.3 porcent of neonates have phlebitis and 46.7 porcent do not have it. There exists a relationship between the knowledge level and the presence of phlebitis (value p>0.10).